Manajemen Produksi Usaha Rengginang Singkong Di Desa Sumbertempur Kecamatan Wonosari Kabupaten Malang - Robertus Harefa (Fakultas Pertanian, 2022)
The development of food processing industry in Indonesia supported by agricultural natural resources, capable of producing various processed products that can be created and developed from local or regional natural resources. Currently in some Asian countries many food products are lifted from local food types and processed traditionally. Home industry companies are small companies run by families or small groups such as home industries. As time goes on in the business world make companies to start thinking about quality business concepts. Business concepts will be of quality when management is well executed in line with changes in decision-making undertaken by the company, especially in companies engaged in household-scale industries. The formulation of the problems are: the production management cassava chips business in the group of farm women Budi Makmur already arranged well,? How is the implementation of production management function of cassava chips business in group of farmer farmer of Budi Makmur at Sumbertempur Village of Wonosari District of Malang Regency. The Respondent shown in this study were all members of the Budi Makmur farmer group as actors producing cassava chips.